2019
DOI: 10.2147/opth.s229708
|View full text |Cite
|
Sign up to set email alerts
|

<p>Short-Term Changes in Intraocular Pressure After Intravitreal Injection of Bevacizumab for the Treatment of Retinopathy of Prematurity</p>

Abstract: PurposeTo evaluate short-term changes in intraocular pressure after intravitreal injection of bevacizumab for retinopathy of prematurity.Patients and methodsThis study was a prospective case-series. Consecutive infants underwent intravitreal injection with bevacizumab for type 1 retinopathy of prematurity at a university hospital. Intraocular pressure was measured with tonometer at baseline, at 1 min, and at 3, 10, 30 and 60 mins after injection.ResultsFive patients (four boys) were enrolled in this study. Mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…We should also consider the safety of IVC while conducting therapies. To our knowledge, only a few studies have reported an IOP increase after anti-VEGF injection in infants ( Kato et al, 2019 ; Obata et al, 2019 ; Ozdemir et al, 2021 ). No studies have investigated IOP increase after conbercept injection in infants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We should also consider the safety of IVC while conducting therapies. To our knowledge, only a few studies have reported an IOP increase after anti-VEGF injection in infants ( Kato et al, 2019 ; Obata et al, 2019 ; Ozdemir et al, 2021 ). No studies have investigated IOP increase after conbercept injection in infants.…”
Section: Discussionmentioning
confidence: 99%
“…According to this study, IVI in premature newborns with ROP may not require IOP measurement after all. ( Obata et al, 2019 ). The dose commonly administered in the ROP trial is half the adult dose.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation